ẢNH HƯỞNG CỦA THỜI GIAN TRỒNG ĐẾN SINH TRƯỞNG, PHÁT TRIỂN CỦA NẤM TRÂN CHÂU (Agrocybe aegerita): EFFECTS OF PLANTING TIME ON GROWTH AND YEILD OF SOUTHERN POPLAR MUSHROOM (Agrocybe aegerita) - Hường, Lê Thị Thu; Minh, Vũ Tuấn (Tạp chí điện tử Khoa học và công nghệ nông nghiệp, 2021)
Nghiên cứu được thực hiện trong vụ Xuân Hè tại trường Đại học Nông Lâm, Đại học Huế nhằm xác định được thời vụ thích hợp cho sinh trưởng, phát triển của nấm Trân Châu tại Thừa Thiên Huế. Thí nghiệm được bố trí theo phương pháp hoàn toàn ngẫu nhiên (CRD), gồm 5 công thức với 5 thời điểm cấy giống khác nhau trong tháng 4 và tháng 5 là 1/4; 10/4; 20/4; 30/4 và 10/5, 3 lần lặp lại, mỗi lần lặp theo dõi 10 bịch. Kết quả cho thấy công thức I, thời điểm cấy giống vào 1/4 cho kết quả tốt nhất. Thời gian phủ kín nguyên liệu 43,26 ngày, thời gian xuất hiện quả thể 57,53 ngày và thời gian quả thể trưởng thành và thu hái 65,87 ngày. Chiều dài quả thể đạt 10,69 cm, đường kính quả thể 3,99 cm và trọng lượng quả thể đạt 90,28 g/cụm quả thể, không xuất hiện mẫu nhiễm. Năng suất đạt 225,70 kg/ tấn nguyên liệu khô dẫn đến lãi ròng thu được 13,92 triệu đồng, cao hơn so với các công thức cùng nghiên cứu. ABSTRACT The experiment was carried out during the Summer-Autumn season at University of Agriculture and Forestry, Hue University to determine the suitability of planting time for the growth performation of Southern Poplar mushroom in Thua Thien Hue province. The experiment was arranged in completely randomized design, including 5 treatments, which were 5 different seedling propagation times of April 1st; April 10th; April 20th; April 30th and May 10th in 3 replications and 10 monitoring bags per each replication. The results showed that the experimental treatment I, which were inoculation time on April 1st, gave the best results compared to other experimental treatment such as the time mycelium covered material at 43.26 days; The time to appear mushroom body reached 57.53 days and the time to mature and harvest of mushroom body was 65.87 days; The length of the mushroom body at 10.69cm, the mushroom body diameter at 3.99cm and the weight of the mushroom body gave 90,28 g/mushroom cluster; infection rate gave 0%. The yield was 22.57% compared to the volume of dry material led to the net profit got 13,92 million VND, higher than all of treatments in the same study.